2013
DOI: 10.1088/0031-9155/58/17/5821
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of characteristic prompt gamma rays emitted from oxygen and carbon in tissue-equivalent samples during proton beam irradiation

Abstract: The purpose of this work was to characterize how prompt gamma (PG) emission from tissue changes as a function of carbon and oxygen concentration, and to assess the feasibility of determining elemental concentration in tissues irradiated with proton beams. For this study, four tissue-equivalent water-sucrose samples with differing densities and concentrations of carbon, hydrogen, and oxygen were irradiated with a 48 MeV proton pencil beam. The PG spectrum emitted from each sample was measured using a high-purit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 25 publications
5
46
1
Order By: Relevance
“…The photon energy spectrum has a continuous component decreasing above 7 MeV and neutrons decreasing strongly above 100 MeV. The high-energy gamma rays are listed by Kozlovsky et al [6] and Polf [7] The distal end of gamma distribution and the Bragg peak in the PMMA target are at the same depth; as shown in Fig. 3, the deposited energy with Bragg peak of the 160 MeV proton beam is plotted in black square and gamma distribution in green circle.…”
Section: Basic Physics and Principlementioning
confidence: 93%
“…The photon energy spectrum has a continuous component decreasing above 7 MeV and neutrons decreasing strongly above 100 MeV. The high-energy gamma rays are listed by Kozlovsky et al [6] and Polf [7] The distal end of gamma distribution and the Bragg peak in the PMMA target are at the same depth; as shown in Fig. 3, the deposited energy with Bragg peak of the 160 MeV proton beam is plotted in black square and gamma distribution in green circle.…”
Section: Basic Physics and Principlementioning
confidence: 93%
“…The photon spectrum presents a continuum component and several de-excitation lines. Such lines have different intensities depending on the traversed tissue, thus allowing for the determination of its composition, in particular the oxygen concentration [70]. As an example, Figure 13 shows the Figure 13.…”
Section: Prompt Photon Detectionmentioning
confidence: 99%
“…Initial studies have found a good correlation between dose delivery and prompt-gamma emission, 9,10 and small shifts in the Bragg peak position can be detected by measuring prompt-gamma emission during treatment. 11,12 Recent studies have also shown that the intensities of the characteristic prompt-gamma spectral lines from individual elements are directly proportional to the concentration of the elements in tissue, 13 so prompt-gamma imaging could provide a path to spectroscopic analysis of irradiated tumors and healthy tissues.…”
Section: In Vivo Imagingmentioning
confidence: 99%